Association between spoligotype-VNTR types and virulence of Mycobacterium bovis in cattle - Garbaccio, Sergio Gabriel; Macias, Analía; Shimizu, Ernesto; Paolicchi, Fernando; Pezzone, Natalia; Zapata, Laura; Abdala, Alejandro Ariel; Tarabla, Hector Dante; Peyru, Maite; Caimi, Karina Cynthia; Zumarraga, Martin Jose; Canal, Ana María; et al. (Taylor & Francis, 2019)
Mycobacterium bovis is the causative agent of bovine tuberculosis, a disease that affects approximately 5% of Argentine cattle. The aim of this research was to study if it is possible to infer the degree of virulence of different M. bovis genotypes based on scorified observations of tuberculosis lesions in cattle. In this study, we performed association analyses between several parameters with tuberculosis lesions: M. bovis genotype, degree of progression of tuberculosis, and animal age. For this purpose, the genotype was determined by spoligotyping and the degree of bovine tuberculosis gross lesion was quantified with a score based on clinical observations (number, size, and location of granulomas along with histopathologic features). This study was performed with naturally infected cattle of slaughterhouses from three provinces in Argentina. A total of 265 M. bovis isolates were obtained from 378 pathological lesion samples and 192 spoligotyping and VNTR (based on ETR sequences) typing patterns were obtained. SB0140 was the most predominant spoligotype, followed by SB0145. The spoligotype with the highest lesion score was SB0273 (median score of 27 ± 4.46), followed by SB0520 (18 ± 5.8). Furthermore, the most common spoligotype, SB0140, had a median score of 11 ± 0.74. Finally, the spoligotype with the lowest score was SB0145 (8 ± 1.0). ETR typing of SB0140, SB0145, SB0273, and SB0520 did not subdivide the lesion scores in those spoligotypes. In conclusion, SB0273 and SB0520 were the spoligotypes with the strongest association with hypervirulence and both spoligotypes were only found in Río Cuarto at the south of Córdoba province. Interestingly, there is no other report of any of these spoligotyes in Latin America.